Removal of Cu(II) and Ni(II) from Solution Using Aegal-Marmelose Fruit Shell Substrate - Gharde, B.D.; Gholse, S.B.; Patil, P.V. (Asian Journal of Chemistry, 2016)
The dried and powdered Aegal-marmelose fruit shell substrate is concentrated with 1% NaOH and the resin product so obtained is efficient in removing Cu(II) and Ni(II) from the solution. The metal ions uptake increases with increase in pH of the solution. It is observed that the maximum sorption efficiency of aegal-marmelose was found to be 5 and 6, respectively. It was found that more than 60% of the metal ions are removed by the substrates from the solution instantaneously by using packed column of the substrates. The metal ions concentration from the wastewater can be reduced to very low levels conforming to the acceptable water quality standards.